Morphological and genetic variability of Baetis (Rhodobaetis) braaschi Zimmermann, 1980 (Ephemeroptera: Baetidae) - Sroka, Pavel; Martynov, Alexander V.; Godunko, Roman J. (Zootaxa, 2012)
Specimens of Baetis (Rhodobaetis) braaschi Zimmermann, 1980 from the three distant geographic regions (Crimean Pen-insula, Eastern Ukraine and Caucasus) are investigated and compared using a methodological approach combining mor-phological and molecular (partial mtDNA COI sequences) data. Intraspecific variability in several morphologicalcharacters is recognized and described, whereas COI sequences are found to be very uniform. The amount and distributionof the changes of COI sequences do not follow the pattern of morphological variability and/or geographic origin of thespecimens. This indicates that analysis of the changes in the COI sequence can contradict the pattern of morphologicalcharacters commonly used for the discrimination of the individual Rhodobaetis species. As a basis for the future taxonom-ic changes concerning subgenus Rhodobaetis, it is advised (where possible) to critically evaluate both molecular and morphological data.